SELF-NARRATIVES OF BRAZILIAN DEAF PEOPLE: APPLICATION OF THE HYPOTHESES OF SOCIOANALYSES - PEDROSA, CLEIDE EMILIA FAYE (Society Register, 2020)
The objective of the study is to apply eight hypotheses of the socioanalysis for the interpretation and critical social reading of the "self-narratives" of deaf applicants to Higher Education at the Federal University of Sergipe (UFS-Brazil). It is located in the theoretical-methodological field of Critical Discourse Analysis (CDA), and Deaf Studies (DS). We will analyze a narrative of a deaf subject, corpus collected in 2014, in the college entrance examination for the Brazilian Sign Language Course (LIBRAS), and adopt this methodological guideline, to define object of study; identify areas of interfaces that meet the objectives; select the categories of each area of interface; establish the dialogue between categories; identify the social meanings constructed in the discourse. The result confirms the role of socioanalysis in seeking to unveil how the practice of social relations and (re)construction of their identities in the struggle for citizenship rights articulate in the deaf individual's life.